Financial and Competition Implications of the European Union’s Green Deal - Voicu D. Dragomir (Amfiteatru Economic)
The European Green Deal, as a priority of the European Commission, includes a plan to make the EU economy sustainable and competitive. The way this can be done is to turn climate and environmental challenges into opportunities. To achieve this goal, massive investments from public funds are foreseen, as well as a reorientation of the financial system and private investments towards projects that reduce the carbon footprint and entail other positive environmental externalities. These intentions have been welcomed by the governments of the member states, the business community, and European citizens.